Assessment of renal function in workers previously exposed to cadmium. Issue 11 (November 1985) - Elinder, C G; Edling, C; Lindberg, E; Kågedal, B; Vesterberg, O
Abstract : Cadmium induced renal effects were examined in 60 workers (58 men, 2 women) previously exposed to cadmium. Tubular damage in the form of beta 2-microglobulinuria was found in 40%, and urinary albumin and orosomucoid increased significantly with increasing urinary cadmium and increasing relative clearance of beta 2-microglobulin. It is suggested that increased albumin excretion is secondary to the tubular damage. In no case was typical glomerular proteinuria found that could be related to cadmium. Histories of renal stones were more common among the workers with high urinary cadmium concentrations. The glomerular filtration rate was measured in 17 of the workers who had pronounced tubular dysfunction. The average glomerular filtration rate for these men was less than the age adjusted predicted value (mean = 84%). Furthermore, there was a significant (p less than 0.05) correlation (r = -0.47) between tubular reabsorption loss and a decreased glomerular filtration rate.